ESTABLISHMENT OF ELECTRONIC COMMERCE AT THE ENTERPRISE - LIASHEVSKA, Viktoriia; DAVIDENKO, Nani (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The study is devoted to the analysis of the state of e-commerce in enterprises. The article considers different approaches to understanding e-commerce as a component of e-business. An attempt is made to determine the place of e-commerce in the formation of the competitiveness of the enterprise. The advantages of using e-commerce for the company are provided, which include: cost reduction, coverage of a larger market segment and others. The advantages that appear to the consumer include: ease of finding stores online; the ability to obtain information about the entire range of the store without the help of a worker; possibility to receive the order at home; round-the-clock loyalty of the store; comparison of prices and quality of goods in different stores at home. Approaches to understanding the essence of e-commerce as a component of business education are considered. The existing models of e-business and their characteristics are given, namely: B2B, B2C, B2A, C2A, C2C. The article also identifies the functions and processes that include e-commerce, which include: ordering catalogs and price lists; connection of Internet applications with the internal system of office work; self-registration of consumers; the possibility of selling goods of different categories via the Internet; order processing according to the standard scheme; making online payments. The trend of growth of e-sales sales for 2018-2020 is illustrated, which indicates an increase in the number of people who use the services of e-commerce companies. Four levels of mutual relations of participants of trade processes and influence of their definition on production activity are resulted. The paper presents a list of disadvantages of using e-commerce for the consumer, which include the security of personal data, the possibility of fraud and others, as well as for the manufacturer, namely: high competition in the market, the possibility of the consumer. fraud, as well as the need for a longer analysis of all performance indicators on the site. The influence of the current state of introduction of e-commerce in the activity of the enterprise on the possible level of potential of development and increase of production indicators is analyzed.